OPTIMASI DAN VALIDASI METODA PENGUJIAN WEDELOLAKTON SECARA KROMATOGRAFI CAIR KINERJA TINGGI DENGAN TEKNIK DETEKSI FLUORESENSI (KCKT - F) - Iiisna Yuliana; Yosi Aristiawan; Iwan Bastiawanz; Julia J. Kantasubrata; Muljadji Agma (Jurnal Kimia Terapan Indonesia, 2012)
Wedelolakton has a wide range of biologicalactivities and used for the treatment of variousailments. In the present study an experiment ofquantitative determination of wedelolactone inherbal extract of Eclipta alba L. Hask has beendeveloped by using RP - HPLC - Fluorimetrytechnique and mixture methanol:0.35% acetic acid(H20) (50:50 vlv) as mobile phase, applied to theherbal extract as inhouse reference materialcandidate samples. The method was validated forthe confirmation of identity (selectivity), linearity,precision, recovery, sensitifity, limit of detectionJKTI, Vol. 14, No.1, Juni 2012and limit of quantitation. Statistical analysis of thedata showed that the method is reproducible andselective for the estimation of wedelolactonedetermination.Keywords: Wedelolactone, HPLC-F, method optimization,method validation, confidence limi